Becoming a self through occupation: Occupation as a source of self-continuity in identity formation. Issue 4 (2nd October 2021) - Maersk, Jesper Larsen
ABSTRACT: For the past 20 years, occupational science researchers have been occupied with the relationship of occupation and identity formation. While this research has led to a diverse and rich body of literature, little attention has been paid to the processes underpinning identity formation through occupation. Within the broader identity literature, self-continuity has been identified as an identity process essential to the foundation of being and the development of a core self. Based on an assemblage of theories positioned in psychodynamic theory, personality psychology, and narrative theory, I present a theoretical construct that describes occupation as a source of self-continuity in identity formation 1) in the 'now' of occupational experience, and 2) through the telling and enactment of occupations in narrative configurations.